Finite element analysis for rocket motor case under internal pressure and thermal loads / M. A. Muhammad ... [et al.] - Muhammad, M. A.; Salleh, Z.; Hamid, A. H. A.; Sujana, M. J.; Kamaludin, K. (Smart Manufacturing Research Institute (SMRI), 2022)
Rocket motor combustion chamber needs to contain very high pressure and temperature due to burning of rocket fuels. For that reason, the combustion chamber is required to withstand the stresses caused by the static and thermal load generated by the burning of the rocket fuels. History demonstrated that a strong rocket motor case can fail due to thermal load neglection. In this study, it has been proven that thermal load affects the stresses produced on the rocket motor case. The stresses produced by the internal pressure and thermal load are called overall stresses. In this study, the thermal analysis was done using ANSYS software with various thickness of CC 2.5, CC 3.5 and C.C 5.0 in two conditions which were the stress due to static stress and the stress due to static and thermal loads. The propellant properties, pressure applied, chamber temperature and heat coefficient were the same in all cases. The maximum von-Mises stress for static load increased from lower to higher thickness with 69.35 MPa, 51.78 MPa and 34.8 MPa for CC 2.5, CC 3.5 and CC 5.0, respectively. When the thermal load was applied, the maximum von-Mises stress increased from 51.78 MPa to 76.87 MPa for CC 3.5, and from 34.80 MPa to 42.61 MPa for CC 5.0. The trend for overall stresses also increased from 68.56 MPa for CC 2.5 to 76.88 MPa for CC 3.5. This study shows that when a thermal load is applied to the rocket body case, the maximum von-Mises stress will also increase.